Tax Avoidance, Financial Performance and Profit Management Effect on Company Value - Dewi Novitasari; Nani Mulyani (Prodi Manajemen Universitas Pamulang, 2022)
Company value is an investor’s perception of the company’s success rate which is often associated with stock price. This research aimed to examine the effect of tax avoidance, financial performance, and profit management on the company value. The research was quantitative. Based on purposive sampling, there were 14 samples from 80 company in the property and real estate sectors which were listed on Indonesia Stock Exchange 2016-2020. In addition, the data analysis technique used data panel regression model using E-Views 9. The research result concluded that partially the tax avoidance and financial performance had effect on the company value. In contrast, profit management had no effect on the company value. Meanwhile, together the tax avoidance, financial performance and profit management have a significant effect on the company value.